KERJASAMA INDONESIA MALAYSIA THAILAND GROWTH TRIANGLE DALAM UPAYA PEMULIHAN EKONOMI PASCA PANDEMI COVID-19 - Sudirman, Arfin; Dermawan, Windy; R, Satrio Gumilar (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Regional economic growth is a support for countries in certain regions. One of the regions with a fairly high level of regional economic growth is Southeast Asia. Regional economic growth in this region cannot be separated from the existence of ASEAN (Association of Southeast Asian Nations) as a regional organization in the region. There is an area of regional economic growth in this region that is interesting to study, namely IMT-GT (Indonesia-Malaysia-Thailand Growth Triangle), a sub-regional cooperation in ASEAN with the membership of Indonesia, Malaysia, and Thailand as three countries with regional borders. The challenge of IMT-GT is economic recovery after the Covid-19 pandemic. This research method is qualitative with data collection techniques through documentation studies, archival studies, and internet search studies. This research found that the dynamics of economic conditions in the three IMT-GT member countries are one of the pillars for post-Covid-19 economic recovery in the region, and the IMT-GT has even become a support for these three countries to get through the COVID-19 pandemic. Cooperation between regions that directly border the ASEAN region is important to establish because it can increase economic growth in the three regions involved in IMT-GT